2008
DOI: 10.1002/lsm.20590
|View full text |Cite
|
Sign up to set email alerts
|

Laser treatments on skin enhancing and controlling transdermal delivery of 5‐fluorouracil

Abstract: Background and Objective: Laser ablation of stratum corneum (SC) enhances transdermal delivery of hydrophilic drugs. The influence of the infrared (IR) (l ¼ 1,064 nm), visible (l ¼ 532 nm), and ultraviolet (UV) (l ¼ 355 nm) radiations of a Nd:YAG laser on transdermal delivery of 5-Fluorouracil (5-Fu) across skin was studied in vitro. Materials and Methods: Pinna skin of the inner side of rabbit ear, was used for the skin permeation. The light source for laser treatment was a Q-switched Nd:YAG laser (Lotis TII … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…Laser and Intense Pulsed Light (IPL) have been common tools for clinical cosmetic therapy [13], and also have been used to improve effectively drug or OCAs transepidermal delivery [14][15][16]. Tuchin et al [17] found that skin permeability could be effectively enhanced by creating an island of limited thermal damage using a flashlamp (IPL) system.…”
Section: Introductionmentioning
confidence: 99%
“…Laser and Intense Pulsed Light (IPL) have been common tools for clinical cosmetic therapy [13], and also have been used to improve effectively drug or OCAs transepidermal delivery [14][15][16]. Tuchin et al [17] found that skin permeability could be effectively enhanced by creating an island of limited thermal damage using a flashlamp (IPL) system.…”
Section: Introductionmentioning
confidence: 99%
“…These include the use of permeation enhancers, employing vesicular drug delivery systems, delivering hydrophilic drugs using microneedles, or augmenting transdermal flux using laser systems. [15][16][17][18][19][20][21][22][23][24] Microdermabrasion, which involves blowing of aluminum oxide crystals or other abrasive substances onto the face and then vacuuming them off, 24peels the stratum corneum, leading to better penetration of topical preparations.…”
Section: Discussionmentioning
confidence: 99%
“…This laser capability has enabled the expansion of its applications to a wide range of bioengineering and biomedicine applications, such as surgery, treatment, drug screening, detection, diagnostics, drug delivery, and analysis [2][3][4][5][6][7][8][9][10][11][12][13]. There are several other advantages as follows.…”
Section: Introductionmentioning
confidence: 99%